WPŁYW MEDIACJI NA EFEKTYWNOŚĆ INSTYTUCJI WARUNKOWEGO UMORZENIA POSTĘPOWANIA KARNEGO - Juszka, Karol (Zeszyty Prawnicze, 2016)
The Influence of Mediation Proceedings on The Effectiveness of the Institution of Conditional Discontinuation of Criminal Proceedings Summary The aim of this article is to present the theoretical and practical aspects of the specifics of mediation proceedings. I present my own research results, consisting of an analysis of the court records for 405 cases on the effectiveness of conditional discontinuance of criminal proceedings within the areas of jurisdiction of the Appellate Court in Kraków in 2003-2009. I will continue the analysis for the successive stages of criminal proceedings.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />